Kebijakan Pendidikan Inklusif Sebagai Jembatan Untuk Mengurangi Anomie Serta Pengembangan Kesejahteraan Emosional Siswa di SMK Tujuh Lima 1 Purwokerto - Himatun Aliyah; Muh. Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article discusses the implementation of inclusive education policies at SMK Tujuh Lima 1 Purwokerto as a solution to reduce anomie behavior among students and enhance their emotional well-being. Anomie, characterized by norm uncertainty and deviant behavior, can be caused by various factors such as family, community, and school environments. By implementing inclusive education that emphasizes equality and acceptance, schools can create a learning environment that supports all students, regardless of their background. Religious education programs, social and emotional learning development, and counseling services are some of the approaches implemented to address anomie and improve student well-being. Research findings indicate that inclusive policies have successfully reduced anomie behavior and increased student engagement with the school, creating a more positive learning atmosphere.